Flourishing of Nias Students: A Phenomenology Study - Luahambowo, Leoni Intan Febriani; Situmorang, Nina Zulida; Mujidin, Mujidin (Universitas Ahmad Dahlan, 2022)
Every person has the power to flourish by maximizing all his or her abilities to obtain a quality and prosperous life—including away-from-home students. The purpose of this study is to determine the factors that influence the flourishing of Nias students in the city of Yogyakarta. This study used a qualitative approach with a phenomenological perspective. The sampling technique used was purposive. Six male away-from-home students were involved, and the inclusion criteria were: 1) participants are from the Nias area; 2) can communicate well; 3) have lived in a boarding house in Yogyakarta for at least one year; 4) have entered at least third semester; 5) aged 18–25 years; 6) willing to be a research participant, as evidenced by a research informed-consent sheet. Data were collected by observation and in-depth interviews with the research sample. Furthermore, this data will be analyzed using content analysis. Nias students who face new environments develop characteristics of positive emotions, engagement, and positive relations in adapting to new environments. Nias students flourish in unfamiliar contexts with family and community support, enabling them to thrive there. Keywords: flourishing; overseas, student